2013
DOI: 10.1145/2400682.2400697
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting reuse locality on inclusive shared last-level caches

Abstract: Optimization of the replacement policy used for Shared Last-Level Cache (SLLC) management in a Chip-MultiProcessor (CMP) is critical for avoiding off-chip accesses. Temporal locality, while being exploited by first levels of private cache memories, is only slightly exhibited by the stream of references arriving at the SLLC. Thus, traditional replacement algorithms based on recency are bad choices for governing SLLC replacement. Recent proposals involve SLLC replacement policies that attempt to exploit reuse ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 20 publications
(29 reference statements)
0
29
0
Order By: Relevance
“…If there are no such blocks, the replacement policy will select the victim block from all blocks in the cache set. This method is similar to a recently proposed inclusive cache management policy [1]. To make a fair comparison, we evaluate the performance of all techniques using this extension in our experiments.…”
Section: Design Issues For Inclusive Cachesmentioning
confidence: 99%
“…If there are no such blocks, the replacement policy will select the victim block from all blocks in the cache set. This method is similar to a recently proposed inclusive cache management policy [1]. To make a fair comparison, we evaluate the performance of all techniques using this extension in our experiments.…”
Section: Design Issues For Inclusive Cachesmentioning
confidence: 99%
“…Despite these efforts, state of the art replacement policies only achieve average improvements within 5% of a commercial algorithm such as NRU, even using a set of benchmarks whose performance is sensitive to replacement [12,1]. Moreover, the fraction of live lines in the SLLC does not increase much with any of the aforementioned techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works [4,5,31,32,34,39,43,56,59,66,73,76] have shown that the traditional LRU replacement policy is highly ineffective for two kinds of workloads. (i) When the working set is larger than the cache size, high-reuse blocks evict each other due to the lack of space, making the cache ineffective.…”
Section: Dynamic Insertion Throttlingmentioning
confidence: 99%
“…Recent works [4,5,31,32,34,39,43,56,59,66,73,76] have shown that the traditional LRU replacement policy is highly ineffective for workloads with cache thrashing and pollution. A large number of works propose insertion policies to solve these problems [16,18,31,32,34,44,56,59,61,66,73,76] by either statistically keeping a fraction of the working set in the cache or exploiting special mechanisms to differentiate the reuse locality of cache blocks and use that information to assist cache block bypassing or insertion.…”
Section: Replacement and Insertion Policies For Llcmentioning
confidence: 99%
See 1 more Smart Citation